Formation mechanism of hydride precipitation in commercially pure titanium. (10th August 2021) - Li, Jingwei; Li, Xiaocui; Sui, Manling
Abstract: Since titanium has high afﬁnity for hydrogen and reacts reversibly with hydrogen, the precipitation of titanium hydrides in titanium and its alloys cannot be ignored. Two most common hydride precipitates in α-Ti matrix are γ-hydride and δ-hydride, however their mechanisms for precipitation are still unclear. In the present study, we find that both γ-hydride and δ-hydride phases with different specific orientations were randomly precipitated in the as-received hot forged commercially pure Ti. In addition, a large amount of the titanium hydrides can be introduced into Ti matrix with selective precipitation by using electrochemical treatment. Cs-corrected scanning transmission electron microscopy is used to study the precipitation mechanisms of the two hydrides. It is revealed that the γ-hydride and δ-hydride precipitations are both formed through slip + shuffle mechanisms involving a unit of two layers of titanium atoms, but the difference is that the γ-hydride is formed by prismatic slip corresponding to hydrogen occupying the octahedral sites of α-Ti, while the δ-hydride is formed by basal slip corresponding to hydrogen occupying the tetrahedral sites of α-Ti.